Numerical model output data for publication "Control of the oceanic heat content of the Getz-Dotson Trough, Antarctica, by the Amundsen Sea Low" - Dotto, T. S.; Kimura, S.; Naveira Garabato, A. (Zenodo, 2020)
Contains MITgcm model output data to reproduce the analyses of the paper "Control of the oceanic heat content of the Getz-Dotson Trough, Antarctica, by the Amundsen Sea Low", by Dotto and co-authors, published in Journal of Geophysical Research-Oceans (doi: 10.1029/2020JC016113). The model simulation is presented and described in Kimura et al. (2017; doi: 10.1002/2017JC012926) and in Dotto et al. (2019; doi: 10.1175/JPO-D-19-0064.s1). See the 'ReadMe.txt' file for a description of the data. : {"references": ["Kimura, S., Jenkins, A., Regan, H., Holland, P. R., Assmann, K. M., Whitt, D. B., et al. (2017). Oceanographic controls on the variability of ice-shelf basal melting and circulation of glacial meltwater in the Amundsen Sea Embayment, Antarctica. Journal of Geophysical Research: Oceans, 122, 10,131\u201310,155, doi: 10.1002/2017JC012926.", "Dotto, T. S., Naveira Garabato, A. C., Bacon, S., Holland, P. R., Kimura, S., Firing, Y. L., et al. (2019). Wind-driven processes controlling oceanic heat delivery to the Amundsen Sea, Antarctica. Journal of Physical Oceanography, doi: 10.1175/JPO-D-19-0064.1.", "Dotto, T. S., Naveira Garabato, A. C., W\u00e5hlin, A. K., Bacon, S., Holland, P. R., Kimura, S., et al. (2020). Control of the oceanic heat content of the Getz\u2010Dotson Trough, Antarctica, by the Amundsen Sea Low. Journal of Geophysical Research: Oceans, 125, e2020JC016113, doi: 10.1029/2020JC016113"]}